Regulation of Sos Activity by Intramolecular Interactions - Corbalan-Garcia, Senena (American Society for Microbiology, 1998)
The guanine nucleotide exchange factor Sos mediates the coupling of receptor tyrosine kinases to Ras activation. To investigate the mechanisms that control Sos activity, we have analyzed the contribution of various domains to its catalytic activity. Using human Sos1 (hSos1) truncation mutants, we show that Sos proteins lacking either the amino or the carboxyl terminus domain, or both, display a guanine nucleotide exchange activity that is significantly higher compared with that of the full-length protein. These results demonstrate that both the amino and the carboxyl terminus domains of Sos are involved in the negative regulation of its catalytic activity. Furthermore, in vitro Ras binding experiments suggest that the amino and carboxyl terminus domains exert negative allosteric control on the interaction of the Sos catalytic domain with Ras. The guanine nucleotide exchange activity of hSos1 was not augmented by growth factor stimulation, indicating that Sos activity is constitutively maintained in a downregulated state. Deletion of both the amino and the carboxyl terminus domains was sufficient to activate the transforming potential of Sos. These findings suggest a novel negative regulatory role for the amino terminus domain of Sos and indicate a cooperation between the amino and the carboxyl terminus domains in the regulation of Sos activity.